Pengaruh penerapan Good Corporate Governance dan Struktur Kepemilikan terhadap Kinerja Keuangan perusahaan manufaktur subsektor Food and Beverage - Shofa Nisrina; Isthi Wahyu Ningtyas; Arjuna Wiwaha (International Journal of Digital Entrepreneurship and Business, 2022)
The objective of this study is to analyze the influence of corporate governance towards financial performance. Good Corporate Governance (GCG) is proxied by institutional ownership, managerial ownership, the audit committee, and independent commissioners. This study uses explanatory research with a quantitative method. The research sample chosen is the food and beverage industry using the purposive sampling method. The secondary data come from the Indonesia Stock Exchange, including financial statements and annual reports. The population of food and beverages companies was listed on the Indonesia Stock Exchange from 2016 to 2019, with a sample size of 14 companies across four years. We use multivariate regression analysis to test the hypotheses. The findings indicated that independent commissioners, audit committees, managerial ownership and institutional ownership could influence ROA positively. Independent commissioners, audit committees could influence ROE positively, however managerial ownership and institutional ownership could influence ROE negatively. The research is useful for companies that have already implemented GCG, and the results show that GCG can influence to financial performance.